Analysis of finger vein variety in patients with various diseases using vein authentication technology. Issue 4 (6th January 2019) - Maeda, Yuichiro; Hasegawa, Toshio; Komiyama, Etsuko; Hirasawa, Yusuke; Tsuchihashi, Hitoshi; Ogawa, Takasuke; Kim, Jonghun; Ando, Seiichiro; Nagasaka, Akio; Miura, Naoto; Ikeda, Shigaku
Abstract : In finger vein authentication technology, near‐infrared rays penetrate the finger and are absorbed by the hemoglobin in blood. The veins appear as dark areas. The finger vein pattern images of patients with various diseases were acquired; a new evaluation method applying image processing technique (" E value") was developed, and it was examined whether the patterns have any characteristics differentiating them from those of healthy volunteers. As a result, low E values appeared in systemic sclerosis, mixed connective tissue disease, Sjögren's syndrome, and polymyositis/dermatomyositis. No statistical reduction in E value was shown in patients with rheumatoid arthritis, pernio (without rheumatic diseases), arteriosclerosis obliterans, diabetes, hypertension, hypothyroidism and alopecia areata. This technology could be used for screening and evaluation of some diseases and their conditions with impaired peripheral venous circulation. E value may be useful as an indicator of venous circulation. Abstract : In finger vein authentication technology, near‐infrared rays penetrate the finger and are absorbed by the hemoglobin in blood. The finger vein pattern images of patients with various diseases were acquired, and a new evaluation method applying image processing technique (" E value") was developed. Low E values appeared in systemic sclerosis, mixed connective tissue disease, Sjögren's syndrome, and polymyositis/dermatomyositis. This technology could be used for screening and evaluation of some diseases and their conditions with impaired peripheral venous circulation.